ANALISIS MANFAAT SOSIAL EKONOMI OBJEK WISATA PANTAI IBOIH SABANG TERHADAP PENDAPATAN PEDAGANG - Zeary Saputra; Ferayanti Ferayanti (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract This study analyzes the socio-economic benefits for traders around the Sabang Iboih Beach tourist attraction and the factors that really dominate it. Some of the variables analyzed in the study are the variable facilities / traders facilities, traders education variables, trader capital variables, traders' health variables and working time variables (trading activities). This study uses primary data with a non-experimental approach. The number of samples is 50 respondents and uses a qualitative descriptive analysis method. The results showed that the health variables and the length of time trading did have a significant relationship to the traders 'income and the traders' capital variables had a significant relationship at 1 percent. The factors that really dominate the magnitude of the socio-economic benefits of the tourism object of Sabang Iboih Beach are the variable length of time implementing the trade and the variable size of merchant capital. While the variables of trader facilities / facilities and trader education variables do not have a significant relationship. The implication of this research is that tourism activities in the Iboih Coast region have high economic and social benefits to the local community. The role of the city government, local government and central government in developing development around the Sabang Iboih Beach tourism object needs to be improvedKeywords: Socio-Economic, Iboih Beach Tourism Objects, Merchant Income